The Effect of Work Overload on Work Stress and Performance of Morowali District General Hospital Employees - Mohammad Ega Nugraha; Armawati; Muhammad Riswandi Palawa; Abdul Rahman; Risnawati (Universitas Muhammadiyah Palu, 2023)
Human resource management is the main factor in carrying out activities. The Regional General Hospital of Morowali district is the largest in Morowali district, which has many civil servants. With the large number of employees, of course, they have very high activity in serving the community. If activity is too high, it will affect employee performance. Furthermore, performance will affect other activities, such as delays in the patient handling process and miscommunication between nurses, medical staff, and other health workers. This dramatically influences a harmonious work atmosphere and can affect employee performance. Excessive workload (work overload), such as the high responsibility that must be maintained by every employee in serving and caring for patients, is also a pressure felt by every employee. With the emergence of higher workloads, employees will feel that the work demands are burdensome, and the behavior of superiors who sometimes pressure employees will make them feel like they are experiencing work stress.